What are effective methods to reduce the incidence of caries?. Issue 9 (September 2015) - Garnier, Christine; Careyva, Beth
Abstract : Evidence‐Based Answer : Toothpastes with fluoride concentrations of 1, 000 to 2, 800 parts per million (ppm) reduce the incidence of caries in children aged ≤16 years (SOR: A, metaanalysis of RCTs). Oral fluoride supplementation reduces the incidence of caries in permanent teeth for children aged 6 to 16 years. However, oral fluoride supplementation is not more effective than fluoride toothpastes or topical fluorides (SOR: B, meta‐analysis of RCTs at risk for bias). Xylitol lozenges may reduce the incidence of new root surface caries in caries‐active adults (SOR: C, secondary analysis in a single RCT).